1970
DOI: 10.3329/jbau.v6i2.4822
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arsenic and its interaction with phosphorus on yield and arsenic accumulation in rice

Abstract: A study was made on the effect of arsenic (As) and As X P interaction in Boro rice and its residual effect in succeeding T. Aman rice. Arsenic was added to soil (having 2.6 ppm initial As) @ 0, 15 and 30 mg As kg -1 from Na 2 HAsO 4 .7H 2 O and phosphorus @ 0, 20, 40, 60 and 80 mg P kg -1 from KH 2 PO 4 . Each pot had received 100 ppm N, 40 ppm K and 25 ppm S from urea, MoP and gypsum, respectively. The grain yield of Boro rice was reduced by 20.6 % for 15 ppm As treatment and 63.8 % due to 30 ppm As. Such red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…Straw N-content was lowest (0.536%) with 0 ppm As treatment and lowest grain N-content (0.470%) was recorded at 30 ppm As treatment. This finding agrees with Begum et al; who reported that the N content in grain and straw increased with increasing addition of arsenic. Different rice varieties showed significant effect on N content in grain but in case of straw it had insignificant effect ( Table 1).…”
Section: Resultssupporting
confidence: 93%
“…Straw N-content was lowest (0.536%) with 0 ppm As treatment and lowest grain N-content (0.470%) was recorded at 30 ppm As treatment. This finding agrees with Begum et al; who reported that the N content in grain and straw increased with increasing addition of arsenic. Different rice varieties showed significant effect on N content in grain but in case of straw it had insignificant effect ( Table 1).…”
Section: Resultssupporting
confidence: 93%
“…1. It has also been reported that the nitrogen concentrations in grain and straw increased with increasing addition of As (Begum et al, 2008). In this experiment, the nitrogen concentration was increased with As treatments and the highest concentrations of nitrogen in grain and shoot were observed in rice plants treated with As and M. minuta, which indicates that the presence of M. minuta did not affect the uptake of nitrogen in rice plants.…”
Section: Effect Of As and M Minuta On Nitrogen Status Of Ricesupporting
confidence: 52%
“…Use of flooded paddies for rice production became preferred over millennia, however, because the flood water protects rice plants from weeds, insects, drought, temperature extremes, and some diseases, including rice blast. Because roots uptake As through phosphorus (P) and silica (Si) transporters, application of P (Begum et al, 2008;Choudhury et al, 2011) and Si fertilizers has also been evaluated as a mitigation strategy (Seyfferth and Fendorf, 2012;Matsumoto et al, 2015;Seyfferth et al, 2016, Seyfferth et al, 2018. Our research focuses instead on identifying rice genes and physiological factors that can reduce grain-As in a variety of production systems.…”
Section: Introductionmentioning
confidence: 99%